Menakar Pengaruh Modernisasi Dalam Implementasi Kebijakan Administrasi Pelayanan Publik Di Kota Kediri - Heylen Amildha Yanuarita; Djoko Susanto (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
This research was conducted to analyze how modernization affects the implementation of public service administration policies, especially in Kediri, East Java. As is well known, from time to time various aspects of life are required to undergo changes to a more modern direction. The research method used is descriptive qualitative method. Descriptive qualitative research is aimed at obtaining an overview of how modernization affects public service administration policies in Kediri. To obtain the necessary data, the authors used a purposive sampling technique so that the sample taken was more focused, assisted by a review of several related previous studies. The results showed that modernization, especially in the field of technology, was sufficient to influence public service administration policies in Kediri.